MORAL VALUES OF PETER PAN THE MUSICAL DRAMA SCRIPT - Shilvani Shilvani; Sudarsono Sudarsono; Eni Rosnija (Universitas Tanjungpura, 2020)
This research aimed to find out the moral values of Peter Pan the Musical drama script and the way those values presented. This research was qualitative description. The corpus was Peter Pan the Musical drama script, written and published by Piers-Chater Robinson under ITM Shows. The script consisted of 78 pages and 3 acts. Miles and Huberman's theory was applied to analyze the data. The research found out that moral values presented in Peter Pan the Musical drama script were about responsibility, bravery, yearning, friendship, kinship, mutual help, positive thoughts and gratitude. The values of friendship and responsibility were emphasized in the scenes, acts, and dialogues. They were delivered explicitly and implicitly, which made the script enjoyable to read. Thus, it is recommended that Peter Pan the Musical drama script be available in the school library a supplement to literary work materials. Keywords: Drama Script, Moral Values, Peter Pan